The Effect Of Web-Quest On Students’ Reading Comprehension And Reading Attitude At SMKN 4 Kendari - Bahidin, Aswira; Tanduklangi, Amri; Rahim, Amiruddin (Journal of Language Education and Educational Technology (JLEET), 2018)
As technology along with the impact of the Internet has led to rapid progress nowadays, educators begin to make use of Internet resources to assist students in learning English as Foreign Language (EFL). WebQuest is one of the Web-based learning tools in education which utilizes the Internet resources. This study aims at investigating the effect of WebQuest model on the students’ reading comprehension achievement and reading attitude at SMKN 4 Kendari. A true experimental research design is employed in this study. The population comprises 138 eleventh graders of SMKN 4 Kendari of academic year 2017/2018. The samples are 2 classes classified into experimental group and control group, and each group consists of 22 students. A cluster sampling technique is applied in selecting the samples. The data are collected by administering reading comprehension pretest and posttest, as well as pre- attitude scale and post- attitude scale. The analysis is done with descriptive statistic. The hypotheses are tested using independent sample t-test. The findings reveals that there is a statistical difference between scores of experimental and control group on the posttest. The mean score of students who learned under WebQuest model is 70.3 (fairly good). This is higher than the mean score of students in control group which is 62.6 (fair). Additionally, the findings shows that majority of the students in experimental group (54.55%) are categorized to have positive attitude towards reading after learning through WebQuest. The first and second alternative hypotheses (Ha1 and Ha2) generated for this study are accepted. The findings implies that the use of WebQuest model do affect the students’ EFL reading comprehension achievement and reading attitude at SMKN 4 Kendari